Mitogenomic analyses support the recent division of the genus Orthotrichum (Orthotrichaceae, Bryophyta) - Jakub Sawicki (Nature Portfolio, 2017)
Abstract A recently presented taxonomical arrangement of the moss genus Orthotrichum Hedw. s.l. substantially changed the traditional view of the taxon that had been accepted throughout the twentieth century. This paper provides the results of mitogenomic studies that strongly support the new taxonomical concept. Comparative analyses presented in this study confirmed the stable structure of moss mitogenomes. Moreover, 17 complete mitogenome sequences were used to identify the major evolutionary groups, including 11 newly sequenced ones, for this study. The analysis of mitochondrial hotspots revealed intron 4 of the cox1 gene to be the most variable non-coding region. The most variable protein-coding genes in the tribe Orthotricheae were ccmFC and tatC. The intergenic and intronic hotspots of Orthotrichum s.l. identified in the present study do not correspond to those described in vascular plant mitogenomes.